ATR Kinase Is a Crucial Player Mediating the DNA Damage Response in Trypanosoma brucei - Marin, Paula Andrea; Obonaga, Ricardo; Pavani, Raphael Souza; da Silva, Marcelo Santos; de Araujo, Christiane Bezerra; Lima, André Arruda; Avila, Carla Cristi; Cestari, Igor; Machado, Carlos Renato; Elias, Maria Carolina (Frontiers in Cell and Developmental Biology, 2020)
DNA double-strand breaks (DSBs) are among the most deleterious lesions that threaten genome integrity. To address DSBs, eukaryotic cells of model organisms have evolved a complex network of cellular pathways that are able to detect DNA damage, activate a checkpoint response to delay cell cycle progression, recruit the proper repair machinery, and resume the cell cycle once the DNA damage is repaired. Cell cycle checkpoints are primarily regulated by the apical kinases ATR and ATM, which are conserved throughout the eukaryotic kingdom. Trypanosoma brucei is a divergent pathogenic protozoan parasite that causes human African trypanosomiasis, a neglected disease that can be fatal when left untreated. The proper signaling and accuracy of DNA repair is fundamental to T. brucei not only to ensure parasite survival after genotoxic stress but also because DSBs are involved in the process of generating antigenic variations used by this parasite to evade the host immune system. DSBs trigger a strong DNA damage response and efficient repair process in T. brucei, but it is unclear how these processes are coordinated. Here, by knocking down ATR in T. brucei using two different approaches (conditional RNAi and an ATR inhibitor), we show that ATR is required to mediate intra-S and partial G1/S checkpoint responses. ATR is also involved in replication fork stalling, is critical for H2A histone phosphorylation in a small group of cells and is necessary for the recruitment and upregulation of the HR-mediated DNA repair protein RAD51 after ionizing radiation (IR) induces DSBs. In summary, this work shows that apical ATR kinase plays a central role in signal transduction and is critical for orchestrating the DNA damage response in T. brucei.